2019
DOI: 10.3390/cells8101139
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Increases Proliferation of Human iPSC-Derived Neuronal Progenitor Cells via Insulin-Like Growth Factor 2 and Independent of the NMDA Receptor

Abstract: The N-methyl-D-aspartate (NMDA) receptor antagonist ketamine offers promising perspectives for the treatment of major depressive disorder. Although ketamine demonstrates rapid and long-lasting effects, even in treatment-resistant patients, to date, the underlying mode of action remains elusive. Thus, the aim of our study was to investigate the molecular mechanism of ketamine at clinically relevant concentrations by establishing an in vitro model based on human induced pluripotent stem cells (iPSCs)-derived neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Decreased levels of a protein upstream of GSK-3, called insulin-like growth factor 2 (IGF2), has previously been implicated in rodent models of depression, with artificial induction of IGF2 expression having protective effects against depressive-like behaviors ( 156 ). IGF2 is upregulated with ketamine in vivo and in vitro ( 150 , 157 )—and this requires the inhibition of GSK-3 as well ( 150 ). Knocking out IGF2 reduces ketamine’s behavioral antidepressant effect, and mice resilient to induced depression show higher amounts of IGF2 than mice that were susceptible to depression paradigms ( 150 ).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased levels of a protein upstream of GSK-3, called insulin-like growth factor 2 (IGF2), has previously been implicated in rodent models of depression, with artificial induction of IGF2 expression having protective effects against depressive-like behaviors ( 156 ). IGF2 is upregulated with ketamine in vivo and in vitro ( 150 , 157 )—and this requires the inhibition of GSK-3 as well ( 150 ). Knocking out IGF2 reduces ketamine’s behavioral antidepressant effect, and mice resilient to induced depression show higher amounts of IGF2 than mice that were susceptible to depression paradigms ( 150 ).…”
Section: Resultsmentioning
confidence: 99%
“…hiPS cell line K3(Si‐Tayeb et al., 2010), IMR90 (Grossert et al., 2019) and BJ2 were routinely cultured on Matrigel (BD, Biosciences) in E8 medium (Gibco) at 37°C with 5% CO 2 . For cell differentiation, the hiPSCs were treated by 12 μM CHIR99021 (Selleckchem) for 48 h.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study found an increase in the densities of neuronal progenitors and newborn GCs in the hippocampal ventral region, together with an increase of expression of specific NMDA and AMPA subunits and mammalian target of rapamycin (mTOR) phosphorylation [ 87 ]. In addition, Grossert et al [ 88 ], through an in vitro model based on human induced pluripotent stem cells (iPSCs), determined an increase of proliferation of NPCs induced by ketamine, where transcriptome analysis revealed significant upregulation of insulin-like growth factor 2 (IGF2) and p11, a member of the S100 EF-hand protein family, which are both implicated in the pathophysiology of depression.…”
Section: Pharmacological Treatments and Ahn In Animal Models And Humansmentioning
confidence: 99%